Female Workers and Mistreatment in Malaysia: A Case of Housemaids from Central Java - Subadi, Tjipto (Universitas Muhammadiyah Surakarta, 2015)
This paper aims to examine the main reason why some Indonesian housemaids are badly treated in Malaysia and to highlight the steps taken by Indonesian and Malaysian governments to cope with this situation. The study uses a phenomenology qualitative approach with a social paradigm definition of micro analysis. This research was conducted in Central Java. The subjects of the research were female workers in Malaysia and their families, government, and the House of Representatives. The techniques of the data collecting included observation, interview, and documentation. The data were analyzed by implementing first order understanding and second order understanding. The data were analyzed with an interactive model: data reduction, data display, and conclusion. The results from this study demonstrate that: 1) the main reason some Indonesian housemaids are badly treated in Malaysia is due to low competency, miscommunication, bad institutional structure, and difference in Act of Indonesian-Malaysian; and 2) the steps taken by Indonesian-Malaysia governments to overcome this situation are by providing assurance for non-problematic employers to employ Indonesian workers, establishing a Cooperation Agency for problem solving, resolving all problems by Indonesian and Malaysian Cooperation Associations, and revising the Memorandum of Understanding (MoU) for Labor Force.